The Wishes and Expression of Gratitude of Youth - Tudge, Jonathan Richard Henry; Freitas, Lia Beatriz de Lucca; Mokrova, Irina L.; Wang, Yudan Chen; O'Brien, Marion (Paidéia (Ribeirão Preto), 2015)
Little research has examined the development of gratitude in youth, and none has related their gratitude to their wishes. We therefore asked 358 7- to 14-year-old North American participants (56% female; 55% White) to write their greatest wish and what they would do for their benefactor. Using chi-square and linear curve estimation, we found that younger youth (aged 7 to 10) were significantly more likely to express hedonistic wishes (desire for immediate gain) and concrete gratitude (not taking the benefactor's wishes into account); older youth (aged 11 to 14) were significantly more likely to wish either for something involving future well-being for themselves or the well-being of others and connective gratitude (taking into account the benefactor's wishes). Within both age groups, there was a significant inverse relation between hedonistic wishes and connective gratitude. This research has implications for encouraging the feeling and expression of connective gratitude.